If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(s-4)-2=2
We simplify the equation to the form, which is simple to understand
-2(s-4)-2=2
Reorder the terms in parentheses
+(-2s+8)-2=2
Remove unnecessary parentheses
-2s+8-2=+2
We move all terms containing s to the left and all other terms to the right.
-2s=+2-8+2
We simplify left and right side of the equation.
-2s=-4
We divide both sides of the equation by -2 to get s.
s=2
| (x+3)(x-2)(x-8)=0 | | n^2+n=22 | | 2y^2-14y+24=0 | | .3x-4x-1=3 | | x+14+x+8=10 | | ex-2=12 | | 2(k-5)-7=1 | | g(p+3)=2x^2+2x+3 | | (4x-3)*(3x-2)= | | 14h-7h=-14 | | 3w+10+2w=5 | | -15/3=x | | -(b--4)=-13 | | 4x^2-21x+22=-4x+4 | | 3j-2j-1=11 | | 24x^2+6x-9=0 | | h(t)=-16t^2+79t+6 | | 42x-14=-17+17x | | 15x-7=5x-13 | | 3r-8=-8 | | v^2+7=0 | | 3x^2+10x+3=19-4x^2+16 | | 6x+2(6x+13)=188 | | 6y+16-2y=18 | | 18-2(8x-7)=22 | | 5t-1=-46 | | 6k+2=3k+5k | | 10x^2+10x+3=19-4x^2+16 | | X-5+2x-4=12 | | 6.09x^2+4.57x-8.86=0 | | (7x-3)(2x+9)=0 | | 7(-6+3z)=42 |